The Role of Standard Specifications in Consumer Protection - Dawood Salman, Researcher. Murtaja; Omar Mohammed, Prof.Dr. Alaa (Basra studies journal, 2026)
This study highlights the pivotal role of standard specifications in consumer protection, serving as both a legal and technical instrument to ensure product safety and quality. It concludes that producers’ compliance with these standards represents an extension of the duty of safety established in comparative jurisprudence. Standard specifications enable consumers to select products that achieve their intended purpose while providing the necessary information for informed decision-making. The study also emphasizes the importance of further developing the legislative framework and strengthening technical oversight to ensure that only compliant products—free from physical or informational risks—are available on the market.